Impact of Non-Steroidal Anti-Inflammatory Drug Usage and Awareness of Side Effects among the Population - Thamer Atiah Sbr Alanazi, Anwar Matar N Alanazi, Fahad Saleh Al-Enzai, Mohammed Mossa Alanazi, Ahmed Aqeel Hadad Alshammari, Ahmad Faleh N Alharbi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used for pain relief, inflammation, and fever reduction. This study examines the patterns of NSAID use and awareness of their side-effects in the adult  population, along with sociodemographic associations.Methods: A cross-sectional study was conducted among 604 adults aged >18 years using a validated questionnaire to collect data on NSAID use and sociodemographic factors.Results: Most respondents were NSAID users (65.7%), predominantly female (53.4%), and aged under 50 years (74.5%). Around 42.6% had received NSAIDs through physician prescriptions. Male gender and smoking were negatively correlated with NSAID use (OR: 0.5, 95% CI: 0.4–0.8, p=0.001; OR: 0.6, 95% CI: 0.4–0.8, p=0.003). Ministry of Health Insurance was associated with NSAID use (OR: 1.6, 95% CI: 1.1–2.6, p=0.03). Awareness of kidney-related side-effects was at 65.1%, while awareness of asthma and allergy risks was at 22.4%.Conclusion: Despite widespread NSAID usage in Jordan, there is limited awareness of their side-effects and interactions, highlighting the need for enhanced patient safety education during physician-prescribed NSAID use.